OPTIMIZATION OF MEDIUM C/N RATIO AND INITIAL PH ON LIPID PRODUCTION BY RHODOTORULA TORULOIDES IN TWO-STAGE CULTIVATION USING RESPONSE SURFACE METHODOLOGY - Maralus Pangaribuan, Gilbert
The sap from oil palm agricultural waste is used to make brown palm sugar. Palm brown sugar can be utilized as a substitute carbon source for microbial-based lipid synthesis since it contains a variety of organic sugars and nitrogen molecules. Microbial-based lipid production has been an alternative source of lipids other than plants. Oleaginous yeast, such as Rhodotorula toruloides, can accumulate lipids up to 70 % of its cell dry weight. Initial medium pH and the C/N ratio are several important parameters that affect microbial-based lipid synthesis. In this research, lipid production by Rhodotorula toruloides will be optimized using response surface methodology. The purpose of this study is to ascertain how three variables—the C/N ratio, the initial medium pH, and the inoculum concentration—affect three responses: cell production rate, maximum cell dry weight, and intracellular lipid content. Ammonium sulfate is the nitrogen source in this study, whereas palm brown sugar is the carbon source. The C/N ratio was varied by varying the concentration of nitrogen source addition at a constant carbon source concentration. Response optimization was carried out under conditions of constant inoculum concentration at 107 cells/mL. According to the ANOVA analysis, the medium's C/N ratio was found to have a strong linear and quadratic effect on the maximum cell dry weight and cell production rate, whereas the medium's initial pH had no significant effect on both responses. The intracellular lipid levels were not significantly affected by the medium's initial pH or C/N ratio. The mathematical model for cell production rate and maximum cell dry weight were significant mathematical models (p<0.05), while the mathematical model for intracellular lipid content was not significant. Response optimization was only carried out at the cell production rate and maximum cell dry weight. Predictions of intracellular lipid content obtained by optimizing maximal cell dry weight were found to be greater than those obtained from optimizing cell production rates. Optimization of the dry weight of this cell resulted in the C/N ratio and initial pH of the medium being 3.7 and 6.5, respectively as optimum conditions. At an inoculum concentration of 107 cells/mL, This condition yields predicted optimal values for the response of cell production rate, maximum cell dry weight, and intracellular lipid content of 0.09 g/L.hour, 12.04 g/L, and 53,48% w/w dry cell, respectively.